If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -6 = 10x + 15 Reorder the terms: -6 + 3x = 10x + 15 Reorder the terms: -6 + 3x = 15 + 10x Solving -6 + 3x = 15 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -6 + 3x + -10x = 15 + 10x + -10x Combine like terms: 3x + -10x = -7x -6 + -7x = 15 + 10x + -10x Combine like terms: 10x + -10x = 0 -6 + -7x = 15 + 0 -6 + -7x = 15 Add '6' to each side of the equation. -6 + 6 + -7x = 15 + 6 Combine like terms: -6 + 6 = 0 0 + -7x = 15 + 6 -7x = 15 + 6 Combine like terms: 15 + 6 = 21 -7x = 21 Divide each side by '-7'. x = -3 Simplifying x = -3
| 8(3/8)=20t(-1/8) | | (a+6)(a+4)= | | 3/7•3 | | 12+(13+y)=25+7 | | 450000-22000x=12000x+(-155000) | | 3x-7=x+14 | | X^2+8x+8=2x | | 3x-7=x+18 | | 450000-22000x=12000x+(155000) | | ydx+(x^2-4x)dy=0 | | (-3ln+lnx)=0 | | x^3-16x-16=0 | | X^2=-12x+64 | | 7+3(x-7)=1-5(x-6) | | -7k=-6k^2 | | -60=x^2-16x | | 2j^2-4j-30=0 | | (4x+3)+57=180 | | (-2x-50)(x+17)=0 | | 3X+42=84 | | 2x=(x+13)+62 | | -1+-4r=-20 | | 1+(6+14)=(1+x)+14 | | -2y+1=y+5 | | 3(32x-256)=0 | | (x-2)(-2x+1)=0 | | 6b^2+19b+15=0 | | 3.9x-6.47=2.5 | | (2x-1)(x-12)=0 | | 6y-2+8y+14+42=180 | | 3/8-1/4x5/6 | | 7+35x=15x+39 |